Psychometric properties of the global rating of change scales in patients with neck disorders: a systematic review with meta-analysis and meta-regression. Issue 11 (25th November 2019) - Bobos, Pavlos; MacDermid, Joy; Nazari, Goris; Furtado, Rochelle
Abstract : Objective: The purpose of this systematic review was to critically appraise and synthesise the psychometric properties of Global Rating of Change (GROC) scales for assessment of patients with neck pain. Design: Systematic review. Data sources: A search was performed in four databases (MEDLINE, EMBASE, CINAHL, SCOPUS) until February 2019. Data extraction and synthesis: Eligible articles were appraised using Consensus-based Standards for the selection of health Measurement Instruments checklist and the Quality Appraisal for Clinical Measurement Research Reports Evaluation Form. Results: The search obtained 16 eligible studies and included in total 1533 patients with neck pain. Test–retest reliability of global perceived effect (GPE) was very high (intraclass correlation coefficient=0.80 to 0.92) for patients with whiplash. Pooled data of Pearson's r indicated that GROC scores were moderately correlated with neck disability change scores (0.53, 95% CI: 0.47 to 0.59). Pooled data of Spearman's correlations indicated that GROC scores were moderately correlated with neck disability change scores (0.56, 95% CI: 0.41 to 0.68). Conclusions: This study found excellent quality evidence of very good-to-excellent test–retest reliability of GPE for patients with whiplash-associated disorders. Evidence from very good-to-excellent quality studies found that GROC scores are moderately correlated to an external criterion patient-reported outcome measure evaluated pre-post treatment in patients with neck pain. No studies were found that addressed the optimal form of GROC scales for patients with neck disorders or compared the GROC to other options for single-item global assessment. PROSPERO registration number: CRD42018117874.